2011
DOI: 10.4297/najms.2011.3167
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatment and targeted therapy in patients with advanced hepatocellular carcinoma

Abstract: Background:Advanced hepatocellular carcinoma (HCC) is a malignancy of global importance: it is the sixth most common cancer and the third most common cause of cancer-related mortality worldwide. Despite decades of efforts by many investigators, systemic chemotherapy or hormone therapy has failed to demonstrate improved survival in patients with HCC.. Ongoing studies are evaluating the efficacy and tolerability of combining Sorafenib with erlotinib and other targeted agents or chemotherapy.Aims:On the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…6,7 Other targeted agents, alone or combined with sorafenib, have been tested in patients with HCC. 8,9 The epidermal growth factor receptor (EGFR) pathway has been implicated in the pathogenesis of HCC. 10,11 EGFR activation may interfere with HCC response to sorafenib, [11][12][13] suggesting that EGFR inhibition may enhance tumor response.…”
Section: 3mentioning
confidence: 99%
“…6,7 Other targeted agents, alone or combined with sorafenib, have been tested in patients with HCC. 8,9 The epidermal growth factor receptor (EGFR) pathway has been implicated in the pathogenesis of HCC. 10,11 EGFR activation may interfere with HCC response to sorafenib, [11][12][13] suggesting that EGFR inhibition may enhance tumor response.…”
Section: 3mentioning
confidence: 99%
“…Although multiple therapeutic modalities are available to treat HCC, mortality is still unacceptably high. Recently, research on tumour signal transduction pathways have revealed important pathway proteins that could be exploited for treatment targets, and these approaches have increased patient survival …”
Section: Introductionmentioning
confidence: 99%
“…In addition, some novel treatment strategies such as molecular targeted therapy and gene therapy have also been developed to fight against HCC (el Tazi et al, 2011;Duan et al, 2013). However, prognosis of many HCC patients remains poor.…”
Section: Discussionmentioning
confidence: 99%